CHARACTERISTICS OF PYROLYSIS OIL BATCH POLYETHYLENE AND POLYSTHYRENE PLASTIC WASTE AT VARIOUS TEMPERATURES - Indah Noor Dwi Kusuma Dewi; Agus Prasetya; Supranto - (ASEAN Journal of Systems Engineering, 2015)
Efforts are being carried out in order to utilize polyethylene (PE) and polystyrene (PS) plastic waste by converting them into fuel or oil. One technology that can be used is pyrolysis. This study aims to (1) determine the quantity and the characteristics of oil from the results of pyrolysis polyethylene (PE) and polystyrene (PS) plastic waste at various temperatures which include characteristics of physics (specific gravity, heating value, flash point, pour point, and kinematic viscosity) and chemical characteristics (composition compounds in oil), (2) determine the optimal conditions of process pyrolysis related to the quality and quantity of oil by pyrolysis, and (3) determine the potential treatment of PE and PS plastic waste by pyrolysis method.The materials used in this study were the type of polyethylene (plastic bags) and polystyrene/styrofoam (for fruits or vegetables) plastic waste. The selected temperature variations are T = 400oC, 450oC, and 500oC. Pyrolysis oil was weighed and measured its volume to obtain v/wo and yield.The results showed that the quantity of pyrolysis oil from polyethylene (PE) plastic waste at temperatures of 400, 450, and 500oC based on v/wo (ml/g) respectively were 0.3429 ml/g; 0.5129 ml/g; and 0.199 ml/g while the results of polystyrene (PS) plastic waste at temperatures of 400, 450, and 500oC respectively were 0.89 ml/g; 0.905 ml/g; and 0.915 ml/g. The results of pyrolysis oil based on yield of polyethylene (PE) plastic waste at temperatures of 400, 450, and 500oC respectively were 33.33 wt%; 38.61 wt%; and 15.55 wt% while polystyrene (PS) plastic waste at temperatures of 400, 450, and 500oC respectively were 80.94 wt%; 79.79 wt%; and 80.14 wt%. While the characteristics shown by the results of pyrolysis oil from PE plastic with a temperature of 400oC were closer to kerosene while at temperatures of 450 and 500oC were closer to the characteristics of diesel fuel. As for pyrolysis oil results of PS plastic with temperatures of 400, 450, and 500oC were closer to the characteristics of gasoline. Optimal conditions of pyrolysis oil related to the quantity of pyrolysis of PE plastic at a temperature of 450oC was obtained when the highest of v/wo and yield respectively were 0.5129 ml/g and 38.16 wt%, while for the pyrolysis of PS did not have any optimal conditions. For, oil produced was relatively constant despite the increasing temperatures. Based on technical analysis, handling PE and PS plastic waste using pyrolysis methods provides benefits to society making it feasible to do.